The Quantitative Analysis of Weather and Soil Moisture Role on Daily Transpiration Dynamics of Oil Palm Varieties (Elaeis guineensis Jacq.) - Pradiko, Iput; Thirafi, Dhaffa Agung; Putra, Eka Tarwaca Susila; Sumaryanto, Sumaryanto; Syarovy, Muhdan; Darlan, Nuzul Hijri; Sujadi, Sujadi; Hutagalung, St Novella Angelica; Farrasati, Rana; Syarif, Afiya Nadhifah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
The purpose of the study is to estimate and determine the in-situ transpiration dynamics of three oil palm varieties, which include DxP Langkat, DyP Dumpy, and DxP PPKS 540, using the Ratio Method (HRM) to measure real-time sap flow (SF). Field observations in Adolina, North Sumatra, were conducted in September, October, and December 2023 to collect data on macro- and microweather and soil moisture at varying distances from sample trees. Vapor pressure deficit (VPD) and solar radiation (QS) were among the key environmental factors that had strong associations with SF. Up to 82.24% of SF variability was explained by VPD and QS. DxP PPKS 540 recorded the highest transpiration rate of 1.70 mm/day because it had a higher leaf area (9.00 m2), and a bigger petiole cross-section (52.50 cm2). DxP Langkat, on the other hand, had the lowest transpiration rate at 1.49 mm/day. The results indicated the significance of VPD and QS in controlling sap flow and suggested that transpiration varied among varieties. This study provides an understanding of the physiological variation among oil palm varieties and a basis for future use in determining genotypes with increased drought resistance and adaptability to enhance resilience in new climatic conditions.